Remote Controlled Home Automation Using Android application via Wi-Fi Connectivity - Khatpe, Mayur; Patel, Brij; Jain, Tushar; Shah, Varun (International Journal of Computer Sciences and Engineering, 2025)
In recent years, the home environment has seen a rapid introduction of network enabled digital technology. This technology offers new and exciting opportunities to increase the connectivity of devices within the home for the purpose of home automation. Mobile devices are ideal in providing a user interface in a home automation system, due to their portability and their wide range of capabilities. They can communicate with a home automation network through an Internet gateway, but cannot directly communicate with devices in the network, as these devices usually implement low power communication protocols, such as ZigBee, WiFi etc. In this project we aims at controlling Home appliances via Android device using Wifi as communication protocol and 8051 via DTMF and also provide security against intrusion when the home host is not at home. We create a user friendly interface for the android device that allows the user to communicate with the Micro. The server will be interfaced with relay circuit board that controls the appliances such as lights and fans running in Home. The communication with server allows the user to select the appropriate device. The server communicates with the corresponding relay. By this we offers a scalable and cost effective Home automation system.